Concentrations and profiles of urinary polycyclic aromatic hydrocarbon metabolites (OH-PAHs) in several asian countries - Guo, Y.; Kuruntha, S.; Alomirah, H.; Moon, H.B.; Minh, T.B.; Mohd, M.A.; Nakata, H.; Kannan, K. (2013)
Concentrations of 12 hydroxylated polycyclic aromatic hydrocarbons (OH-PAHs) were determined in 306 urine samples collected from seven Asian countries (China, India, Japan, Korea, Kuwait, Malaysia, and Vietnam) by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The total concentrations of OH-PAHs found in the seven Asian countries were in the following increasing order: Malaysia (median: 2260 pg/mL) < Japan (4030 pg/mL) < China (5770 pg/mL) < India (6750 pg/mL) < Vietnam (8560 pg/mL) < Korea (9340 pg/mL) < Kuwait (10â170 pg/mL). The measured urinary concentrations of 1-hydroxypyrene (1-PYR) in samples from Malaysia, Korea, and Japan (â¼ 100 pg/mL) were similar to those reported for North America and Western Europe. The concentrations of 1-PYR in urine samples from China, India, and Vietnam were 4-10 times higher than those reported for other countries, thus far. Among the 12 OH-PAH compounds analyzed, hydroxynaphthalene (NAP: sum of 1-hydroxynaphthalene and 2-hydroxynaphthalene) was the dominant compound (accounting for 60-90 of total OH-PAHs), followed by hydroxyphenanthrene (PHEN: sum of 2-hydroxyphenanthrene, 3-hydroxyphenanthrene, 4-hydroxyphenanthrene, and 9-hydroxyphenanthrene 3-16%), 2-hydroxyfluorene (3-20%), and 1-PYR (2-8%). The total daily intakes (DIs) of PAHs were estimated based on the urinary concentrations of their metabolites. The DIs of naphthalene were found to be higher for populations in Korea, Kuwait, and Vietnam (> 10 Î¼g/day) than those of the other countries studied (â¼ 5 Î¼g/day). The DIs of phenanthrene and pyrene (> 10 Î¼g/day) in the populations of China, India, and Vietnam were higher than those estimated for the populations in the other countries studied (â¼ 5 Î¼g/day).